BEDIUZZAMAN SAID NURSI’S METHODOLOGY IN THE DISCOURSE OF MORAL EDUCATION IN HIS THEMATIC EXEGESIS, RASĀ’IL AL-NŪR - Betania Kartika Muflih (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2013)
Abstract: This work investigates the approach used by Imam Bediuzzaman Said Nursi in the discourse on Islamic morality, and to understand his lively scriptural approach to the moral values in which it makes one’s life meaningful and purposeful. This work is aimed to highlight distinctive aspects and features of his approach and methodology used in his Qur’anic exegesis, Rasail al-Nur, which relate to the moral education. It discusses the background, the reason and the purpose behind Imam Bediuzzaman’s approach to the issue at hand. It is also important to note down that his writing is not the result of a merely intellectual enterprise, but also the living answers to problems he has personally experienced. The thesis follows library and textual analysis to address the main problematic. Hence, it concludes that it is necessary to situate Imam Bediuzzaman’s work within the context of Tauhid (Divine Unity) framework, which constitutes the background of his entire system of thought. Indeed, Imam Bediuzzaman’s approach provides a scaffold for a profound understanding and interpretation of the concept of morality and its impact on one’s life and social fabric. Abstrak: Karya ini menginvestigasi pendekatan yang digunakan oleh Imam Bediuzzaman Said Nursi dalam wacana moralitas Islam, dan untuk memahami pendekatan kitab sucinya yang cemerlang terhadap nilai-nilai moral yang membuat kehidupan seseorang bermakna dan bermanfaat. Karya ini juga dimaksudkan untuk menyoroti aspek yang khas dan berbeda dari pendekatan dan metodologi yang digunakannya dalam penafsiran al-Quran, Rasā’il al-Nūr, yang dikaitkan dengan pendidikan moral. Di sini akan dibahas tentang latar belakang, alasan dan tujuan dibalik pendekatan Imam Bediuzzaman terhadap isu tersebut. Juga, penting dicatat bahwa tulisannya bukanlah hasil dari keberanian intelektual semata-mata, melainkan jiga jawaban-jawaban langsung terhadap persoalan-persoalan yang dialaminya secara pribadi. Tesis ini mengikuti analisis pustaka dan tekstual yang difokuskan pada problematika utama. Karena itu, penting utuk menempatkan karya Imam Bediuzzaman dalam konteks kerangka Tauhid, yang merupakan latar belakang dari seluruh sistem pemikirannya. Memang, pendekatan Imam Bediuzzaman menyediakan sebuah penopang untuk sebuah pemahaman dan interpretasi yang mendalam terhadap konsep moralitas dan pengaruhnya bagi kehidupan dan sistem sosial. Keywords: the Qur’an, Rasā’il al-Nūr, New Said, moral education, and jihād.